»Zapadlí vlastenci« by Karl Václav Rais - Všetička, František (Bohemistyka, 2022)
Zapadlí vlastenci (1894) by K. V. Rais begins with temporal incipit, which frames the plot of the novel. The protagonists have birds’ nomina propria. The motif that goes through the whole work is a revelatory motif of a illegitimate child. Other aspects of the composition are diary-like and epistolar elements, as well as the anticipant’s character and significant chapter (13.). The prose work has a character of architectonic triad. From the morphological point of view, the author is close to Alois Jirásek and Julius Zeyer.